1998
DOI: 10.1021/ie980162s
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Fuel from Animal Fat. Ancillary Studies on Transesterification of Beef Tallow

Abstract: Transesterification of beef tallow was investigated. The solubility of ethanol in beef tallow was much higher than that of methanol. At 100 °C the solubility of methanol was 19% (w/w). The solubility of ethanol in beef tallow reached 100% (w/w) at about 68 °C. For the distribution of methanol between beef tallow methyl esters (BTME) and glycerol, the percentage of total methanol in the glycerol phase was higher than that in the fatty acid methyl ester (FAME) phase in a simulated system at room temperature. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
2
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(96 citation statements)
references
References 7 publications
4
83
2
7
Order By: Relevance
“…Assim, países como França, Áustria, Alemanha, Bélgica, Reino Unido, Itália, Holanda, Finlândia, Estados Unidos, Japão e Suécia vêm investindo significativamente na produção e viabilização comercial do biodiesel, através de unidades de produção com diferentes capacidades 6,13,21 e também se pode dizer que para o Brasil esta é uma tecnologia bastante adequada, devido à disponibilidade de óleo de soja e de álcool etílico derivado da cana-de-açúcar. No entanto, a comercialização do biodiesel ainda apresenta alguns gargalos tecnológicos 24 , surgindo como obstáculos para sua comercialização o preço da matéria-prima e os custos operacionais 25 . O Brasil consome cerca de 35 milhões de t/ano de óleo diesel 26 , assim, com ampliação deste mercado a economia de petróleo importado seria expressiva, podendo inclusive minimizar o déficit de nossa balança de pagamentos.…”
Section: Introductionunclassified
“…Assim, países como França, Áustria, Alemanha, Bélgica, Reino Unido, Itália, Holanda, Finlândia, Estados Unidos, Japão e Suécia vêm investindo significativamente na produção e viabilização comercial do biodiesel, através de unidades de produção com diferentes capacidades 6,13,21 e também se pode dizer que para o Brasil esta é uma tecnologia bastante adequada, devido à disponibilidade de óleo de soja e de álcool etílico derivado da cana-de-açúcar. No entanto, a comercialização do biodiesel ainda apresenta alguns gargalos tecnológicos 24 , surgindo como obstáculos para sua comercialização o preço da matéria-prima e os custos operacionais 25 . O Brasil consome cerca de 35 milhões de t/ano de óleo diesel 26 , assim, com ampliação deste mercado a economia de petróleo importado seria expressiva, podendo inclusive minimizar o déficit de nossa balança de pagamentos.…”
Section: Introductionunclassified
“…During the transesterification of beef tallow with methanol the reaction was very slow during the first minute due to the mixing and dispersion of methanol into beef tallow. In the next five minutes, the reaction proceeded very fast (Ma et al, 1998). The production of beef tallow slowed down and reached the maximum value at about 15 min.…”
Section: The Effect Of Reaction Timementioning
confidence: 99%
“…A small amount of soap favors the consumption of catalyst and reduces the catalytic efficiency, as well as causing an increase in viscosity, the formation of gels, and difficulty in achieving separation of glycerol. Ma et al (1998) suggested that the free fatty acid content of the refined oil should be as low as possible, below 0.5%, and Feuge & Grose (1949) also stressed the importance of oils being dry and free of free fatty acids. The use of alkali catalysts in the transesterification of used cooking oil is somewhat limited because the FFA in used cooking oil reacts with the most common alkaline catalysts (NaOH, KOH, and CH 3 ONa) and forms soap.…”
Section: The Effects Of Moisture and Free Fatty Acidsmentioning
confidence: 99%
“…the maximum free fatty acid content must be at most 0.5% (Ma et al, 1998;Bradshaw and Meuly, 1944;Feuge and Grose;1949). This parameter is, nevertheless, less critical than the water content.…”
Section: Alkali-catalyzed Transesterificationmentioning
confidence: 99%